Cryptolemus in the integrated fight against the Australian Grooved Worm (Icerya purchasi Mackall) - L. N. Bugaeva; E. V. Kashutina; T. N. Ignateva (Юг России: экология, развитие)
Aim. To study the possibility of using cryptolemus in an integrated system for combating the Australian grooved worm in the conditions of the southern coast of Crimea.Material  and  Methods.  The  population  of  Icerya  purchasi  Mackall  on plants was determined during regular surveys of agrobiocenoses by counting the number of pest individuals per unit area. The biological effectiveness of cryptolemus from the unique scientific installation «State collection of living entomoacariphages and entomopathogens» in relation to the Australian grooved worm on pittosporum in the conditions of the Southern Coast of Crimea was studied in the following variants: beetle release, larval release and joint release of imago and predator larvae. The possibility of joint use of bioagent and pesticides was studied in the laboratory according to generally accepted methods.Results. It was established that the biological efficacy of Cryptolaemus montrouzieri Muls. in relation to Icerya purchasi Mackall in the conditions of the Southern Coast of Crimea amounted to 50–75% and the possibility of joint use of an entomophage with a number of pesticides is also shown.Conclusion.  The  potential  possibility  of  controlling  the  pest  population with a bioagent, without the use of chemical means of protection, which is especially important in the conditions of a resort area, has been experimentally proven.